2014
DOI: 10.1177/147470491401200306
|View full text |Cite
|
Sign up to set email alerts
|

The Rival Wears Prada: Luxury Consumption as a Female Competition Strategy

Abstract: Abstract:Previous studies on luxury consumption demonstrated that men spend large sums of money on luxury brands to signal their mate value to women and, thus, increase their reproductive success. Although women also spend copious amounts of money on luxuries, research focusing on women's motives for luxury consumption is rather scarce. Relying on costly signaling and intrasexual competition theory, the goal of the current study was to test whether female intrasexual competition in a mate attraction context tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 50 publications
3
59
0
6
Order By: Relevance
“…This might explain investment in beauty and exercise correlated in women but did not relate to self-perceived attractiveness. Hudders et al (2014) found that women invest more in items that improve their physical appearance as a tactic to increase their ability to compete for a mate with other women. In this line, investments in beauty may be a result of intrasexual competition among females, directing women to invest greater resources in order to try to attract or retain a partner, instead of necessarily leading to an increase in self-perception as romantic partners, before the lack of enough amount resources needed to purchase items that could, in fact, improve their appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might explain investment in beauty and exercise correlated in women but did not relate to self-perceived attractiveness. Hudders et al (2014) found that women invest more in items that improve their physical appearance as a tactic to increase their ability to compete for a mate with other women. In this line, investments in beauty may be a result of intrasexual competition among females, directing women to invest greater resources in order to try to attract or retain a partner, instead of necessarily leading to an increase in self-perception as romantic partners, before the lack of enough amount resources needed to purchase items that could, in fact, improve their appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies may employ wider measures, including behavioral patterns and time investment in beauty enhancement. Although a recent study pointed out that women invest greater resources in their appearance in a context of intrasexual competition (Hudders et al 2014), we did not ask the participants about how threatened they feel by their same sex peers. Because of this, we could not investigate if investments in beauty (physical attractiveness improvement) are better described as a self-promotion strategy or as investment in improving appearance (more related to accessories, as clothes, jewelry, and pursues, used to enhance appearance but not being related to change in individuals physical).…”
Section: Discussionmentioning
confidence: 99%
“…And status is positively associated with economic well-being (Frank, 1985), good health (Sapolsky, 2005), and reproductive success (Hudders et al, 2014; Miller, 2011; Newson, 2009). People in remote, rural societies might not need to display status through conspicuous consumption since interactions occur between people who know each other; but the need to display status will probably gain importance as traditional societies transmogrify in the face of globalization (Godoy et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…As yet, marketing and communication researchers have not displayed a deep interest in the evolutionary causes of consumer behavior, although there have been a few exceptions (e.g., Griskevicius, Shiota, & Nowlis, 2010;Hantula, 2003;Hudders, De Backer, Fisher, & Vyncke, 2014;Saad, 2007;Saad & Gill, 2000;Vincke, 2016). However, it is possible to provide a clearer understanding of a consumption phenomenon such as childlike behavior by accepting the assumption that individual variation in behavioral dispositions can be considered from an evolutionary perspective (Buss, 2009;Nettle, 2005).…”
mentioning
confidence: 99%